Pengaruh Kredibilitas Celebrity Endorser Natasha Wilona terhadap Brand Image Produk Kecantikan - Catherine Angelica; Riris Loisa (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Social media, which is currently active as a means of buying and selling online, raises activities to promote products that will be sold by several public figures who are often called celebrity endorsers. The credibility of a celebrity endorser greatly influences the reputation a company wants to buy. A celebrity endorser is expected to be a spokesperson for the brand and be able to create a good image for the brand itself. Brand image can affect product positioning so that every company always tries to present a different and unique image compared to other similar products. This study aims to see how far the influence of celebrity endorser credibility on the brand image of beauty products. The method used is a quantitative method with accidental sampling technique by distributing questionnaires to 100 respondents using Scarlett Whitening in West Jakarta. Validity, reliability, and normality tests are the requirements for analysis in this study. From these data were analyzed by correlation coefficient test, coefficient of determination test, F test, and T test. The results obtained from this study indicate the credibility of a celebrity endorser has an effect of 51% on the brand image of the advertised product. The most prominent dimension is the